2017
DOI: 10.1080/21645515.2017.1335840
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of immunological mechanisms exerted by HBsAg-HBIG therapeutic vaccine combined with Adefovir in chronic hepatitis B patients

Abstract: An HBsAg-HBIG therapeutic vaccine (Yeast-derived Immune Complexes, YIC) for chronic hepatitis B (CHB) patients has undergone a series of clinical trials. The HBeAg sero-conversion rate of YIC varied from 21.9% to 14% depending on the immunization protocols from 6 to 12 injections. To analyze the immunological mechanisms exerted by 6 injections of YIC, 44 CHB patients were separately immunized with YIC, alum as adjuvant control or normal saline as blank control, with add on of antiviral drug Adefovir in all gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…HBsAg-HBsAb immune complex therapeutic vaccine has been established in our laboratory [28] and in phase IIB clinical trials, six injections per month followed for six months have been shown to result in HBeAg seroconversion rates of around 20% [29] . In addition, this vaccine was shown to decrease the percentage of regulatory T cells and to increase T helper cells and cytotoxic CD8 + T cells [19] . Here, adding a mouse version of this therapeutic vaccine to the "sandwich" strategy efficiently induced both HBsAgspecific humoral and cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HBsAg-HBsAb immune complex therapeutic vaccine has been established in our laboratory [28] and in phase IIB clinical trials, six injections per month followed for six months have been shown to result in HBeAg seroconversion rates of around 20% [29] . In addition, this vaccine was shown to decrease the percentage of regulatory T cells and to increase T helper cells and cytotoxic CD8 + T cells [19] . Here, adding a mouse version of this therapeutic vaccine to the "sandwich" strategy efficiently induced both HBsAgspecific humoral and cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The "sandwich" treatment regime was administered three times as indicated and mice were sacrificed three weeks after the third treatment ( n = 5/group) (a). The mice serum was collected at day 0, 2, 5,9,12,15,19,23,28,34,41,55 tably, after the three treatments, a significant reduction of HBeAg levels was only observed in the sandwich group compared to the control TDF group ( p = 0.01; Fig. 4 c).…”
Section: Combination Therapy With G12 Antibody Tdf and Hbsag-hbsab Imentioning
confidence: 95%
See 1 more Smart Citation
“…In the IC-immunized group of patients, increases in Th1 and Th2 cells among the CD 4 + T cells were associated with decrease in Treg cells and increase in Tc1 and Tc17 cells among the CD 8 + T cells. 86…”
Section: Preventive and Therapeutic Vaccines Based On Icmentioning
confidence: 99%
“…Further novel protein-based vaccine candidates incorporating HBsAg and HBcAg and currently in clinical trials are Theravax (DV-601), combined with a saponin-based ISCOMATRIX adjuvant [79], and ABX203, administered by the intranasal route [80]. In addition, an innovative vaccination approach consists of the yeast-derived HBsAg and human anti-HBs immunoglobulin complex combined with alum adjuvant (HBsAg-HBIG) [81,82].…”
Section: Therapeutic Vaccinationmentioning
confidence: 99%